Comparative Analysis of Building Envelope Energy Models Under Future Climate Scenarios - Taştemir, İbrahim Agah; Köymen, Erdem; Yaşa, Enes; Taştemir, İbrahim Agah; Köymen, Erdem (Springer, 2026)
Thermal comfort in buildings is one of the most important architectural design parameters to consider. The building envelope is an important building component that affects the energy efficiency of residential buildings. The building envelope component is the building element that separates the internal and external environments of the building, provides the necessary comfort conditions for the internal environment of the building, and is used to control environmental factors such as heat, light, and sound in order to create the indoor comfort required by the occupants. One of the main ways to reduce the cooling and heating energy expenditure to provide thermal comfort in buildings is to make the right decisions regarding the building envelope, where the heat transfer in the building takes place, and to control the heat transfer in the building envelope. The aim of this study is to show the effect of envelope alternatives with similar thermal transmittance values but different thermal properties, using different building elements, on energy efficiency under different climatic conditions and with future climate scenarios. For this purpose, the effect of thermal capacity is evaluated by energy simulation in three different climatic zones with different temperature and humidity levels in Turkey. In the analytical evaluation, building envelope alternatives with different indoor thermal capacities and similar thermal transmittance values (U-values) were analyzed in terms of heating and cooling energy loads in the summer and winter periods with current, 2050 and 2080 climate scenarios. We compare the annual changes in heating and cooling loads for different building envelopes in terms of their dynamic thermal heat capacity, based on simulations.
6th Central European Symposium on Building Physics, CESBP 2025 / Editors:Balázs Nagy, Zsuzsa Szalay -- Springer -- 2026.
Keywords: Building envelope; Climate design; Energy efficiency; Heat capacity